Alumina-extracted residue-derived silica foams with ultra-large pore volume for highly superior post-combustion CO2 capture. (15th May 2022) - Li, Xiangyu; Wang, Zhiqing; Mei, Yangang; Feng, Ru; Liu, Zheyu; Huang, Jiejie; Dong, Libo; Fang, Yitian
Graphical abstract: Highlights: A mesoporous silica foam was fabricated from the alumina-extracted residue of coal ash. The sorbent impregnated with 80% TEPA obtained the highest adsorption capacity. The sorbent impregnated with PEI showed faster adsorption kinetics than that of TEPA. Recycling alumina-extracted residue for CO2 capture owned both environmental and cost advantages. Abstract: Sodium silicate solution obtained by alkali dissolving alumina-extracted residue (AR) of coal ash was used to fabricate mesoporous silica foam (MSF). The MSF supports can load with 80 wt% amine polymers due to its ultra-large pore volume, thus obtaining the maximum CO2 adsorption capacity of 6.46 mmol/g under 75 °C and dry 100% CO2 atmosphere. Moreover, the sorbents presented fast adsorption kinetics, low adsorption heat and regeneration heat, and stable adsorption-desorption cycle performance. Amine impregnated MSF derived from AR was a promising alternative for post-combustion CO2 capture of power plant flue gas in the future.